(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the fascinating realms of paremy and paremiology, the study of proverbs and their usage. It elucidates the significance of proverbs in various cultures, their cognitive implications, and the methodologies employed in paremiological research. By examining the methods, results, and implications of paremiological studies, this article sheds light on the enduring wisdom encapsulated within these concise expressions of folk wisdom.